Characteristics of the participants in mass sporting events in Vietnam - Tri Le, Truong (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to examine the characteristics of athletes and spectators at mass sports competitions, focusing on aspects such as quantity, age, gender, educational level, occupation, and income to provide a comprehensive demographic overview. The study employed a sociological survey method, sampling 10 localities out of 63 provinces and cities across Vietnam. The survey included 520 spectators (Group 1) and 220 athletes (Group 2), resulting in a total sample size of 740 participants. The results are illustrated using graphical representations. The majority of spectators at mass sport events are aged 23 to under 60, whereas athletes show a more even age distribution, indicating lower student participation in spectating. Men significantly outnumber women. Most participants hold high school or university degrees, with the largest group being unskilled workers. Students, freelancers, and retirees are more evenly distributed. Professional field participants make up 35.5% of the total. Income-wise, most participants are middle to high-income earners, with nearly half earning between 5 and 10 million VND per month, and 42.3% earning over 10 million VND. Low-income and very high-income individuals are mostly spectators, while medium to high-income individuals are more likely to be athletes.